Jungle School - Laird, Elizabeth; Davison, Roz.; Sim, David (New York : Crabtree Pub., 2006)
New at school, Jani shows her monkey classmates all the ways that her wheelchair makes her special.
School Library Journal.
1.9
K-3
Keywords: Monkeys -- Juvenile fiction; People with disabilities -- Juvenile fiction; Schools -- Juvenile fiction; Wheelchairs -- Juvenile fiction; Monkeys -- Fiction; People with disabilities -- Fiction; Schools -- Fiction; Wheelchairs -- Fiction; Handicapped -- Fiction; Monkeys -- Fiction; School stories; Wheelchairs -- Fiction